TINGKAT KEDISIPLINAN SISWA DALAM MENGIKUTI EKSTRAKURIKULER SEPAK BOLA DI SMA SANTO FRANSISKUS ASISI PONTIANAK - Leonardo Leonardo; Ahmad Atiq; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem discussed in this study is how big is the level of student discipline in participating in football extracurricular activities at the Santo Fransiskus Asisi Pontianak High School. The purpose of this study was to determine the level of student discipline in participating in football extracurricular activities at the Santo Fransiskus Asisi Pontianak High School. The approach in this study is a quantitative approach, because this research is presented with numbers. With survey research forms. The population in this study were students who took part in the extracurricular football activities of SMA Santo Fransiskus Asisi Pontianak, amounting to 40 people. The sampling technique in this study uses saturated sampling. The number of samples used is in accordance with the total population of 40 people. In a research data collection technique used is indirect communication techniques.The results of this study indicate there is a level of discipline of students in joining football extracurricular activities at the St. Francis Asisi High School Pontianak reaching an actual score of 1039 from an ideal score of 1400 meaning reaching 74.21% of what it should be, thus belonging to the "Good" category. This can be interpreted that in all aspects of the level of student discipline in following the football extracurricular activities at the Santo Fransiskus Asisi Pontianak High School, including both. The results of the study can be explained by exercise discipline. Keywords: Discipline, Extracurricular, Football